Teori Kriminologi Teori Kriminologi: Teori Asosiasi Diferensial, Teori Ketegangan, Teori Kontrol Sosial, Teori Subkultur, Teori Diri: Teori Asosiasi Diferensial, Teori Ketegangan, Teori Kontrol Sosial, Teori Subkultur, Teori Diri - Achmad Fathoniansyah, Aqilla; Khasrima Putri, Linda; Habiba Romli Angelita, Rizky; Rahmanita Sihab, Audina (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Criminology theory has various approaches to understanding the causes of criminal behaviour. This study aims to analyse Differential Association Theory proposed by Edwin Sutherland, which emphasises that criminal behaviour is learned through social interaction with individuals involved in criminal practices. Meanwhile, Anomie Theory proposed by Émile Durkheim explains how instability of social values can trigger criminal acts. Social Control Theory highlights the importance of social bonds in preventing deviant behaviour, while Subculture Theory explains how certain groups develop norms and values that differ from the wider community, which can encourage criminal behaviour. Finally, Personality Theory focuses on psychological factors that influence individuals, suggesting that certain personality characteristics can contribute to the tendency to commit crimes. Each theory offers unique insights that are important for understanding the complexity of criminal behaviour in social and individual contexts. A deeper understanding of criminology theory also increases public awareness of how to overcome the challenges of crime.